Communication systems for scientific collaboration and mobility - Aceituno-Aceituno, Pedro, (El Profesional de la información, 2019)
Given the effectiveness shown for the creation of collaborative environments of social network sites and the scarcity of work on their use by researchers, the purpose of this article is the analysis of the use of communication systems in scientific collaboration by the collective most involved in scientific mobility. A survey among the Spanish groups most involved in scientific mobility (n = 415) was carried out to analyze the communication systems they use for their colla- boration. Scientists use social network sites scarcely for their collaboration, although these can serve as a complement to face-to-face communication systems. The main framework for their collaboration is meetings, congresses, and works- hops. Our results can contribute to articulate effective policies to improve this mobility for the benefit of the processes of creation and transfer of scientific knowledge of the countries of origin.